United States Securities Law (Open textbook library., 2014)
The United States Securities Code and Regulations appear in Title 15 of the United States Code and Title 17 of the Code of Federal Regulations. This publication was made with data provided by the United States government on the Office of Law Revision Counsel as well as the eCFR.